ATP6V0B promotes the tumorigenesis of bladder cancer by activating PAQR4/PI3K/AKT signaling - Xinsheng Wang; Yanqing Qu; Yanbo Sun; Tong Yang; Wei Wang; Xinmeng Dou; Yong Jia (BMC Cancer)
Abstract Background ATPase H+ transporting V0 subunit b (ATP6V0B) is an essential component of the vacuolar ATP multi-protein complex (V-ATPase) associated with energy metabolism. However, information on its role and mechanism of action in bladder cancer (BCa) and other tumors is not clear. Methods In this study, we evaluated the expression of ATP6V0B in BCa and its correlation with patient survival outcomes by performing public database analysis, as well as, RT-qPCR and Western blotting assays. We also investigated the effect of altering the level of expression of ATP6V0B on the malignant behavior of BCa cells at the cellular level by conducting the CCK-8 assay and Transwell assay. In vivo experiments involved subcutaneous injection of stable ATP6V0B-knockdown BCa cells into nude mice to assess the influence of ATP6V0B on tumorigenesis. Additionally, bioinformatics analysis was combined with other methods to predict that ATP6V0B may modulate signaling pathways. Results The findings showed that the expression of ATP6V0B increased in BCa tissues, and patients exhibiting high levels of this protein had a poorer prognosis. Additionally, our results showed that ATP6V0B functions as an oncogene and stimulates the proliferation, invasion, and migration of BCa cells in vitro. In vivo animal studies showed that downregulating ATP6V0B hindered the growth of BCa. Regarding the mechanism of action of ATVP60VB, we found that ATVP60VB can activate the PI3K/AKT signaling pathway through Progestin and AdipoQ Receptor Family Member 4 (PAQR4) -mediated upregulation. Conclusion To summarize, the results of this study indicated that an increase in the level of expression of ATP6V0B in BCa tissues and cells is associated with unfavorable patient prognosis due to its tumor-promoting effects via upregulation of the PAQR4/PI3K/AKT signaling pathway.